2002
DOI: 10.1046/j.1365-2516.2002.00651.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors predictive of death among HIV‐uninfected persons with haemophilia and other congenital coagulation disorders

Abstract: Historically, the leading cause of death among persons with haemophilia and other congenital coagulation disorders was uncontrolled bleeding. Mortality was associated with severe deficiency of coagulation factors VIII or IX and especially with high-titre antifactor neutralizing antibodies (inhibitors). The catastrophic contamination of plasma donor pools with human immunodeficiency virus (HIV) resulted in acquired immunodeficiency syndrome replacing haemorrhage as the leading cause of death among persons with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…16 A study of the causes of death in people with hemophilia in Sweden during 1957 to 1980 reported that intracranial hemorrhage accounted for 38% (15/39) of all deaths in people with severe hemophilia, 17 and the proportion of deaths involving intracranial hemorrhage was only slightly lower than this in the present study, at 34% (84/250). Intracranial hemorrhage was also found to be the leading cause of death in studies covering this time period of people with hemophilia at all ages in the Netherlands, 11 the United States, 18,19 and France. 20 The French study 20 reported 3 deaths from intracranial hemorrhage in neonates during the 1990s.…”
Section: Mortality From All Causes and Life Expectancymentioning
confidence: 82%
“…16 A study of the causes of death in people with hemophilia in Sweden during 1957 to 1980 reported that intracranial hemorrhage accounted for 38% (15/39) of all deaths in people with severe hemophilia, 17 and the proportion of deaths involving intracranial hemorrhage was only slightly lower than this in the present study, at 34% (84/250). Intracranial hemorrhage was also found to be the leading cause of death in studies covering this time period of people with hemophilia at all ages in the Netherlands, 11 the United States, 18,19 and France. 20 The French study 20 reported 3 deaths from intracranial hemorrhage in neonates during the 1990s.…”
Section: Mortality From All Causes and Life Expectancymentioning
confidence: 82%
“…The value of this analysis mainly relies in providing novel data on mortality in the Italian population of PWH that adds up to those already available from countries like UK, Canada, US, Spain, the Netherlands. These results can be compared with studies that did evaluate mortality and causes of death in the whole population of PWH [11–15], as well as and with those that analysed specific subpopulations, namely HCV‐ or HIV‐infected PWH. Results cover the whole history of the therapeutic approach to PWH, spanning from the dramatic increase in life expectancy between the 1960s and 1980s as a result of the widespread availability of replacement therapy with plasma‐derived concentrates to the catastrophic contamination of these concentrates by HIV and HCV in the 1980s.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports on mortality in PWH [6–15]. However, while half of them focussed on mortality in specific subpopulations of patients such as those infected with HIV and HCV and yet others excluded PWH with blood‐borne infections [6–10], only very few studies analysed mortality and causes of death in the whole haemophilic population, especially after the end of the era of the highest risk of blood‐borne virus transmission [11–15]. With the aim of comparing the periods before and after the use of infectious coagulation factors, and also considering that none of the available studies was conducted in Italy, we chose to review mortality rates and causes of death among Italian PWH during the study period 1980–2007, and to analyse the factors which contributed to the variation of the mortality rate and related improvement in life expectancy.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in patients with hemophilia and cardiovascular disease, the presence of coronary disease and cardiovascular morbidity and mortality were associated with the same traditional risk factors as in the general population. Cardiovascular disease in patients with hemophilia has attracted more interest in recent years, because decreased mortality from bleedings and viral infections has resulted in a longer life‐expectancy and consequently longer exposure to cardiovascular risk factors [7–9].…”
Section: Introductionmentioning
confidence: 99%